Poster No. 104 Impact of pre-treatment with a P2Y12 receptor inhibitor on delay to CABG surgery in a real-world population with non-ST segment elevation acute coronary syndrome. (21st October 2022) - Gomes, Daniel; Rocha, Bruno M L; Ferreira, Jorge; Paiva, Mariana Sousa; Santos, Rita Reis; Santos, Marina Raquel; Cunha, Gonçalo; de Araújo Gonçalves, Pedro; Fevereiro, Susana; Trabulo, Marisa; Aguiar, Carlos; Sousa-Uva, Miguel; et al.
Abstract: Background: ESC guidelines for non-ST elevation acute coronary syndromes (NSTE-ACS) recommend against P2Y12 pre-treatment receptor inhibitors (P2Y12i) in patients undergoing early invasive management (< 24 h). The rationale is, in part, to prevent bleeding complications and the delay of coronary artery bypass graft surgery (CABG) in patients with suitable anatomy. This study aims to analyze the impact of P2Y12i pre-treatment on delay to CABG surgery in a real-world population with NSTE-ACS. Methods: Single-centre retrospective cohort of consecutive patients with NSTE-ACS undergoing invasive evaluation in 2019. Those with previous CABG ( n = 31) or non-obstructive coronary disease ( n = 57) were excluded. Results: Total cohort included 262 patients (mean age 68 ± 12 years, 69% male, 15% with unstable angina and mean GRACE score 134 ± 35). Median time from first medical contact to angiography was 2 (1–4) days. Overall, 168 (64%) patients underwent percutaneous coronary intervention, 47 (18%) were proposed for CABG and the remainder received conservative management. All patients considered for CABG received pre-treatment with P2Y12i, either clopidogrel or ticagrelor. Median time from angiography to CABG was 12 (7–15) days. Six patients experienced recurrent angina (13%) and 2 (4%) died before surgery due to refractory ventricular fibrillation. Those who underwent CABG under P2Y12i effect were more likely to receive blood and platelets transfusions (64.7% vs. 28.6%, P = 0.017 and 82.4% vs. 21.4%, P < 0.001, respectively), although there were no differences regarding major bleeding. Conclusion: Pre-treatment with P2Y12i was a potential driver of CABG delay in our cohort. In the real-world, adopting the new recommendations of withholding pre-treatment might decrease this delay.